Efficacy of adjunctive topical liposomal clarithromycin on systemic Glucantime in Old World cutaneous leishmaniasis: a pilot clinical study - Hakamifard, Atousa; Radmehr, Reza; Sokhanvari, Fatemeh; Sherkat, Fatemeh; Hariri, Amirali; Varshosaz, Jaleh; Shahmoradi, Zabihollah; Feizi, Awat; Abtahi-Naeini, Bahareh; Pourmahdi-Boroujeni, Mahsa (Frontiers in Pharmacology, 2023)
Aim: This study aimed to investigate the effects of topical liposomal clarithromycin in combination with Meglumine antimoniate (Glucantime®) on cutaneous leishmaniasis (CL) lesions. Methods: This pilot, a randomized double-blinded clinical trial, was conducted on patients with CL lesions. Patients were randomly assigned to two groups: the first group received liposomal clarithromycin for 28 days and Glucantime, while the second group received Glucantime and a placebo. Afterward, patients were followed up for 1.5, 3, and 6 months later and were evaluated for recovery time, induration, and size of the lesions. Results: Sixty patients with CL lesions were divided into two separate groups with 30 members and were studied. Within-group analysis revealed that recovery time in the clarithromycin group was 26.65 ± 5.12 days, while in the placebo group was 32.84 ± 24.43, which statistically was insignificant (P = 0.18). Lesion size comparison in the first and last follow-ups reduced in both groups: 7.73 ± 4.31 to 0.48 ± 0.50 in the clarithromycin group (P = 0.006) and 5.47 ± 5.83 to 0.76 ± 0.88 in the placebo group (P = 0.03). Moreover, the size of lesions in the intervention group was significantly reduced compared to the placebo group (P = 0.02). Recognizable induration reduction was observed in the clarithromycin group (2.60 ± 0.77 to 1.0 ± 0.00). No adverse effects attributable to clarithromycin were reported.The administration of liposomal clarithromycin in combination with systemic Glucantime had a significant beneficial effect on reducing lesion size in leishmaniasis. Further studies on larger populations are recommended.